Advances in the surgical approach to brain tumors: A review of minimally invasive and neuronavigation navigation techniques - Decaria, Filyppo Ferreira Porto; Correia , Beatriz Susigan; Rocha, Diógenes Gustavo Vila Barbosa da; Benez, Manuela Rodrigues; Batista, Jéssica Trevisan Covre Simão; Raitez, Skhar Rubens Ribeiro; Furian, Maria Eduarda Alegretti; Pamplona, Mariane Arakawa; Silva , Francisca Paula Batista da; Monteiro, Whendy Arantes; Constantini, Pamela Judith Silva (Seven Editora, 2023)
Brain tumors are a significant health issue and pose a major challenge in neurosurgery. Advances in surgical techniques have enabled neurosurgeons to improve patient outcomes and minimize the risks associated with traditional open surgery. This article will review the latest developments in minimally invasive surgical techniques and neuronavigation technology for the treatment of brain tumors. DOI:https://doi.org/10.56238/interdiinovationscrese-074